2020
DOI: 10.3390/cancers12113085
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin Signaling in Cancer

Abstract: The multifunctional adipokine chemerin exerts key functions in inflammation, adipogenesis and glucose homeostasis[...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Chemerin has a significant function in cancer development, yet its role in carcinogenesis is poorly understood. It turns out that the concentration of chemerin can be decreased or increased during the development of many cancers and can show both protective and promoting effects on the development of carcinogenesis [ 232 , 243 , 244 ]. The potential role of chemerin in carcinogenesis is shown in Figure 7 .…”
Section: Chemerinmentioning
confidence: 99%
“…Chemerin has a significant function in cancer development, yet its role in carcinogenesis is poorly understood. It turns out that the concentration of chemerin can be decreased or increased during the development of many cancers and can show both protective and promoting effects on the development of carcinogenesis [ 232 , 243 , 244 ]. The potential role of chemerin in carcinogenesis is shown in Figure 7 .…”
Section: Chemerinmentioning
confidence: 99%
“…The dual role of chemerin in cancer development is that high serum chemerin levels may indicate increased survival in patients with tumors such as breast cancer, ovarian cancer, hepatocellular carcinoma (HCC), and adrenocortical carcinoma (ACC), while high chemerin expression suggests poor prognosis in patients with gastric cancer and non-small cell lung cancer (NSCLC) (171). For PC, Kiczmer et al ( 53) evaluated serum chemerin levels in 27 patients with PC, 10 patients with CP, and 36 control volunteers and found that chemerin levels were significantly elevated in patients with PC (Table 1).…”
Section: Chemerinmentioning
confidence: 99%
“…(Jacenik & Fichna, 2020), and its main functions were initially found in immune response, adipogenesis, as well as glucose and lipid metabolism (Jacenik & Fichna, 2020). Recently, Chemerin has been reported to be involved in the pathogenesis of inflammation and in a wide range of diseases, such as cancer, preeclampsia, and polycystic ovary syndrome (Luo et al, 2021; Quan et al, 2021; Treeck & Buechler, 2020; Yue et al, 2023). The serum contents of Chemerin are significantly elevated in various inflammatory diseases and contribute to the development of inflammation by aggregating different types of inflammatory cells (chemotaxis of dendritic cells and macrophages) at the site of inflammation (Su et al, 2021).…”
Section: Introductionmentioning
confidence: 99%